Masculine Ways of Being at Home: Hobbies, Do-It-Yourself and Home Improvement in Argentina (1940–70) - Pérez, Inés (2015)
Masculinity and domesticity are often thought of as notions in tension. In Argentina, during the central decades of the twentieth century, they were mingled in a model of domesticity sustained in a "democratization" of wellbeing, home ownership and free time. This association relied on the inclusion of new technologies and activities within the home, related to hobbies, do-it-yourself and home improvement projects, which were regarded as signs of family respectability. On the basis of 45 life stories, and establishing a counterpoint through the representations that can be traced in popular magazines from the period, this article analyzes the objects, tasks and spaces considered "masculine" within the domestic space. The article presents the most relevant features of the model of domesticity that favored men's presence at home, highlighting the ideal of togetherness on which it was based. Then, it explores the contrast between domestic tasks, objects and spaces designed for men and women, emphasizing the tensions men's presence at home gave place to. Finally, it analyzes masculine ways of being at home while avoiding family life. As the article shows, "masculine" domestic objects and spaces played a significant role in confirming one's status in a scenario of intense social mobility.